Shortage of Rental Housing in Germany: Causes, Instruments, Implications - Stephan L. Thomsen; Daniel Vogt; Lars Brausewetter (Wirtschaftsdienst)
Abstract The current state of the German rental market for housing is the subject of an ongoing public debate. Over the last few years, an excess demand in urban areas has led to an increase in rental prices. Since the majority of Germans rent, this development affects a large number of households. A set of different housing policy interventions has been provided by the German government that aims to alleviate the disequilibrium. This article analyses the main reasons for the problem and discusses selected housing policy measures in terms of potential impact. Our conclusion is that a policy mix would be useful in, first, increasing the number of available apartments (necessity) and, second, addressing its distribution adhering to social criteria (sufficiency).